2015
DOI: 10.1038/srep08584
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of the heme biosynthesis pathway for the production of 5-aminolevulinic acid in Escherichia coli

Abstract: 5-Aminolevulinic acid (ALA), the committed intermediate of the heme biosynthesis pathway, shows significant promise for cancer treatment. Here, we identified that in addition to hemA and hemL, hemB, hemD, hemF, hemG and hemH are also the major regulatory targets of the heme biosynthesis pathway. Interestingly, up-regulation of hemD and hemF benefited ALA accumulation whereas overexpression of hemB, hemG and hemH diminished ALA accumulation. Accordingly, by combinatorial overexpression of the hemA, hemL, hemD a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
87
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 100 publications
(91 citation statements)
references
References 50 publications
3
87
1
Order By: Relevance
“…Heme was also responsible for proteolytic degradation of HemA via the Lon and ClpAP proteases, thus limiting endogenous ALA production [25]. Recent studies on heme regulation revealed that endogenous HemA and HemL are part of a C 5 pathway that is tightly regulated by the downstream genes particularly via ALA dehydratase, encoded by hemB gene that is considered as a key feedback inhibitory node in the heme synthesis pathway [26]. By contrast, intracellular ALA biosynthesis was successfully increased in the pHemAL-DyP strain.…”
Section: Enhancing Endogenous Ala Biosynthesis In Recombinant E Colimentioning
confidence: 99%
“…Heme was also responsible for proteolytic degradation of HemA via the Lon and ClpAP proteases, thus limiting endogenous ALA production [25]. Recent studies on heme regulation revealed that endogenous HemA and HemL are part of a C 5 pathway that is tightly regulated by the downstream genes particularly via ALA dehydratase, encoded by hemB gene that is considered as a key feedback inhibitory node in the heme synthesis pathway [26]. By contrast, intracellular ALA biosynthesis was successfully increased in the pHemAL-DyP strain.…”
Section: Enhancing Endogenous Ala Biosynthesis In Recombinant E Colimentioning
confidence: 99%
“…Introduction 5-Aminolevulinic acid (ALA), the precursor for the biosynthesis of tetrapyrroles, has received extensive attention because of its broad applications in the fields of agriculture and medicine (Zhang et al 2015). Many researches have been carried out for biological production of ALA using recombinant Escherichia coli strains expressing heterogeneous 5-aminolevulinic acid synthase (ALAS), the key enzyme in ALA synthesis.…”
mentioning
confidence: 99%
“…palustris, as well as oxygenic photosynthetic bacteria, such as Anacystis nidulans are also reported [1]. It is well known that photosynthetic bacteria have the ability to synthesize tetrapyrrol via 5-ALA intracellularly from glycine and succinate by ALA-synthetase (Shemin pathway) [14,15,26]. Wild strains have very low yield of 5-ALA, so optimization of the production is needed.…”
Section: Introductionmentioning
confidence: 99%